Protocol amending the Convention Between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of the Republic of Uzbekistan for the Avoidance of Double Taxation and the Prevention of Fiscal Evasion with Respect to Taxes on Income and Capital Gains, Signed at Tashkent on 15 October 1993, London, 24 January 2018. ([2018-08-01]) - Unknown
No abstract available